Influence of Alpine highland pasture on the fatty acid and terpene composition of milk and Plaisentif cheese from various Piedmont farms - Gai F.; Battelli G.; Bottero M.T.; Civera T.; Dalmasso A.; Pattono D.; Peiretti P.G. (Forage resources and ecosystem services provided by Mountain and Mediterranean grasslands and rangelands, 2014)
The aim was to characterize, monitor and certify Plaisentif, known as the “cheese of the violets”, produced with raw milk from cows fed on pastures in the Chisone and Susa valleys (NW Italy) when violets are in bloom. A preliminary study was conducted over the summer of 2013 on five Alpine dairy farms to determine the fatty acid (FA) composition and terpenoid profile for the first growth cycle in permanent meadows, and for milk and ripened cheese. The pastures showed a wide diversity both in FA and terpenoid profiles. Among FAs, the most abundant were α-linolenic acid (from 40 to 61% of total FA) and linoleic acid (from 13 to 31% of total FA), while p-Cymene and α-Pinene were the most important terpenoids. As far as milk and cheese FA content are concerned, palmitic and oleic acid accounted on average for 47.2 and 47.7% of total FA, respectively. Healthy FAs, such as α-linolenic acid and conjugated linoleic acid, showed mean values of 1.4-2.1% of total FA, respectively. Terpenoid profiles of milk and cheese were very similar, even though a slight concentration of some terpenes in cheese was observed compared to the corresponding milk. Moreover, Alpine highland pasture modified the FA and terpenoid profile of Plaisentif cheese, while processing milk into ripened cheese did not affect its FA composition and terpene profile with the exception of eicosapentaenoic, butyric and caproic acids among FA, and limonene, p-Cymene and allo-Ocimene among terpenes.
Joint Meeting of the "Mountain Pastures, Mediterranean Forage Resources (FAO/ESCORENA-CIHEAM) and Mountain Cheese" Network, 2014/06/24-26, Clermont-Ferrand (France)